HBR's 10 must reads on managing people. (Harvard Business Review Press, 2011)
HBR's 10 Must Reads on Managing People will inspire you to:Tailor your management styles to fit your people, Motivate with more responsibility, not more money,Support first-time managers, Build trust by soliciting input, Teach smart people how to learn from failure, Build high-performing teams, Manage your boss